Effectiveness of gold nanoparticles in prevention and treatment of oral mucositis in animal models: a systematic review - Choudhury, M.; Brunton, Paul; Schwass, D.; Pletzer, D.; Ratnayake, J.; Dias, G.; Tompkins, G. (2024)
Background: Oral mucositis remains a significant complication during cancer therapy with no effective treatment. Gold nanoparticles offer anti-inflammatory, antioxidant properties with low toxicity. This study systematically reviews the literature assessing gold nanoparticles in the management of oral mucositis in animal models. Methods: A literature search was undertaken using MEDLINE, Embase, PubMed, and Web of Science databases, using the format for Systematic Review Centre for Laboratory Animal Experimentation. Prior to the review, the protocol was registered in the systematic review register, PROSPERO (registration no. CRD42021272169). Outcome measures included ulceration, histopathological scores, inflammatory mediators, microbial growth, and pain. Study quality was analysed by SYRCLE risk-of-bias tool. Results: Only one study met the inclusion criteria, documenting reduction in ulceration, inflammatory, and oxidative biomarkers. Exposure to AuNPs prevented inflammatory response induced by 5-fluorouracil in oral mucosa of hamsters. However, a high risk of bias necessitates further research. Conclusion: This review identifies a potential therapeutic strategy for prevention and management of oral mucositis. It also provides future direction for gold nanoparticle research in oral mucositis; however, there is lack of sufficient evidence to derive any conclusion. Research with standardized parameters including nanoparticle size, capping agent, surface charge, and appropriate oral mucositis animal models will establish risk–benefit balance and margin of safety for therapeutic use of gold nanoparticles for oral mucositis.